2018
DOI: 10.1038/s41598-018-24691-7
|View full text |Cite
|
Sign up to set email alerts
|

Polarization noise places severe constraints on coherence of all-normal dispersion femtosecond supercontinuum generation

Abstract: Supercontinuum (SC) generated with all-normal dispersion (ANDi) fibers has been of special interest in recent years due to its potentially superior coherence properties when compared to anomalous dispersion-pumped SC. However, care must be taken in the design of such sources since too long pump pulses and fiber length has been demonstrated to degrade the coherence. To assess the noise performance of ANDi fiber SC generation numerically, a scalar single-polarization model has so far been used, thereby excluding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
78
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 49 publications
4
78
0
Order By: Relevance
“…In ANDi SC generation, it has been shown that the pulse duration, fiber length, and peak power have a critical influence on the noise properties [12,14], e.g., the anticipated coherent spectra are only obtained for sufficiently short pulse durations and fiber lengths. To see the effect of pump laser amplitude noise on the coherence and the requirements on the fiber length and pulse parameters, we simulate a wide parameter space and calculate for each case the spectrally averaged coherence given by [12,20]:…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In ANDi SC generation, it has been shown that the pulse duration, fiber length, and peak power have a critical influence on the noise properties [12,14], e.g., the anticipated coherent spectra are only obtained for sufficiently short pulse durations and fiber lengths. To see the effect of pump laser amplitude noise on the coherence and the requirements on the fiber length and pulse parameters, we simulate a wide parameter space and calculate for each case the spectrally averaged coherence given by [12,20]:…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately Gonzalo et al just briefly mentioned the effect of pure amplitude noise of the pump laser for one specific pulse duration and fiber length and no specific simulation including the amplitude noise was shown and no general study conducted [14]. In this work, we therefore present a comprehensive study of the influence of the noise of a mode-locked pump laser on the coherence and RIN of the SC spectrum generated in an ANDi fiber.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…On the other hand, there is particular interest in combining the chalcogenide fiber platform with polarization-preserving properties as this will enable polarization-dependent applications in interferometric techniques, gas and pressure sensing, integrated-optic devices and also polarization-sensitive OCT [25][26][27][28][29][30]. Polarization-maintaining fibers also help in minimizing detrimental effects such as polarization noise and instability [31]. There are several ways of introducing strong birefringence in the fiber for polarization maintaining propagation.…”
Section: Introductionmentioning
confidence: 99%